Study of Intercropping System and In Situ Organic Matter Application on Coffee Agroforestry at Citarum Watershed, West Java, Indonesia - Kusnendi, Faizal Shofwan; Supijatno, Supijatno; Wachjar, Ade; Hidayat, Yayat; Suseno, Sugeng Heri (Journal of Tropical Crop Science, 2020)
Agroforestry-based coffee is one of the conservation efforts to restore the damages at the Citarum watershed. Planting annual crops between coffee rows could potentially contribute income for the growers during the immature non-productive coffee growth. The aims of the research is to study the effect of various types of agroforestry models in the upstream Citarum watershed on the growth of coffee, and growth and yields of the intercrops. The research was conducted in September 2018 to June 2019 at the upstream Citarum watershed of Tarumajaya Subdistrict Kertasari, Bandung Regency, West Java, Indonesia. The research was arranged with a randomized block design with two factors. The first factor was the cropping system, i.e. coffee monoculture, coffee and corn, coffee and sweet corn, coffee and red beans, and coffee and habanero chili. The second factor was organic matter application, i.e. with and without application of in situ organic matter. The results of the research showed that coffee intercropped with habanero with application of in situ organic matter had the best vegetative growth, indicated by taller plants, more leaves, increased leaf P and Mg levels, and the maximum income from the intercrop. Coffee intercropped with corn with application of in situ organic matter had a maximum corn production but had the lowest income. Therefore, the model of coffee intercropped with habanero chili with application of in situ organic matter was the best model from several intercropping systems tested.